Blood Lead Levels and Healthy Complaint in Printing Workers of Unipress Surabaya - Mika Vernicia Humairo; Soedjajadi Keman (JURNAL KESEHATAN LINGKUNGAN, 2017)
Lead is found in the printing ink, it gets into the human body through skin absorption and ingestion. Blood lead level > 10 Î¼g/dL causes health disturbances. The purpose of this study was analyzed blood lead level and healthy complaints in printing worker of Unipress Surabaya. This research was observational analytic with cross sectional approach. The subject was printing production process employees and administration employees. Population of production process employees were 10 people and administration employees were 7 people. Whereas, sample of production process employees were 9 and administration employees were 6. The determination of the sampling used simple random sampling. Data analyzed with chi-square test and t-independent test. Blood lead level of production process employees have  ± SD = 6.16 ± 0.37 Î¼g/dl, whereas the blood lead level of administration employees have ± SD = 6.0±0.18 Î¼g/dl. Based on the results by t-independent test (p = 0.371) which indicated there was no difference blood lead level of production process employees and administration employees. Based on the test results by chi-square (p = 0.005) which indicated there was difference in central nervous system disturbances of study group and control group. It is concluded that blood lead level in printing worker of Unipress Surabaya are normal. Though it can suggested to use gloves while working, increase hygiene and sanitation behavior, reducing smoking habit, as well as routine health check up to see the blood lead leve